Magnitude of low back pain and associated factors among primary school teachers in Borama City, Somaliland: an institutional-based cross-sectional study - Seid Yimam Ali; Mekonin Meskelu Shegere; Ahmed Moumin Abdilahi; Najah Bouh Farah; Bilan Abdi Adem; Asma Jemal Nour (BMJ Open, 2025)
Objectives The goal of the study was to determine the magnitude and contributing factors of low back pain among primary school teachers in Borama Town, Somaliland.Design An institution-based descriptive cross-sectional study design was employed. Simple random sampling was used to select the study units from each school.Setting The study was conducted in Borama, Somaliland.Participants A total of 268 primary school teachers participated in the study.Outcome measures The primary outcome of the study was the prevalence of low back pain.Results The study found that 51.5% of school teachers had low back pain. There was a strong link between low back pain and having a higher Body Mass Index (adjusted OR (AOR)=2.63) and stress at work (AOR=3.34). Sleep disturbance (AOR=1.73), lifting heavy materials (AOR=1.67) and a history of low back injury (AOR=2.12) were also significant predictors of low back pain.Conclusion More than half of primary school teachers had low back pain over the past 12 months. Higher Body Mass Index, history of low back injury, stress at work, lifting heavy material and sleep disturbance were significant and independent predictors of low back pain among primary school teachers.